Clostridium difficile PCR ribotypes 001 and 176 - the common denominator of C. difficile infection epidemiology in the Czech Republic, 2014 - Krutova, Marcela; Matejkova, Jana; Kuijper, Ed J; Drevinek, Pavel; Nyc, Otakar; Czech Clostridium difficile study group (Euro surveillance, 2016)
In 2014, 18 hospitals in the Czech Republic participated in a survey of the incidence of Clostridium difficile infections (CDI) in the country. The mean CDI incidence was 6.1 (standard deviation (SD):7.2) cases per 10,000 patient bed-days and 37.8 cases (SD: 41.4) per 10,000 admissions. The mean CDI testing frequency was 39.5 tests (SD: 25.4) per 10,000 patient bed-days and 255.8 tests (SD: 164.0) per 10,000 admissions. A total of 774 C. difficile isolates were investigated, of which 225 (29%) belonged to PCR ribotype 176, and 184 isolates (24%) belonged to PCR ribotype 001. Multilocus variable-number tandem repeat analysis (MLVA) revealed 27 clonal complexes formed by 84% (190/225) of PCR ribotype 176 isolates, and 14 clonal complexes formed by 77% (141/184) of PCR ribotype 001 isolates. Clonal clusters of PCR ribotypes 176 and 001 were observed in 11 and 7 hospitals, respectively. Our data demonstrate the spread of two C. difficile PCR ribotypes within 18 hospitals in the Czech Republic, stressing the importance of standardising CDI testing protocols and implementing mandatory CDI surveillance in the country.
Keywords: PCR ribotype 176; oznamovací povinnost; nemocnice; Humans; Polymerase Chain Reaction; binary toxin; ribotyping; feces; CDI surveillance; Mandatory Reporting; Czech Republic; Minisatellite Repeats; Clostridium Infections; průjem; incidence; Hospitals; PCR ribotype 001; Česká republika; ribotypizace; klostridiové infekce; Feces; MLVA; elektroforéza kapilární; C. difficile infection; polymerázová řetězová reakce; Ribotyping; Diarrhea; lidé; Electrophoresis, Capillary; minisatelitní repetice; Incidence; Clostridioides difficile